Pelaksanaan Kegiatan Pelayanan Administrasi Kependudukan Melalui Aplikasi Klampid New Generation Di Kelurahan Genting Kalianak Kota Surabaya - Adinda Prameiswary; Tukiman Tukiman (Jurnal Kabar Masyarakat, 2023)
The Surabaya City Population and Civil Registry Office partners with the Ministry of Education, Culture, Research and Technology in the MSIB Batch 4 program. This activity is designed for students who want to assist the Surabaya City Government in providing Population Administration services at the Population and Civil Registration Service, by going directly as a form of service to public. In MSIB activities with the Surabaya City Population and Civil Registration Service, students participate in the population administration service process through the Klampid New Generation Application. During the internship, students get 1 KNG account to help sub-district staff process population administration requests for residents of Genting Kalianak. Through this MSIB program, the author as an apprentice student hopes to be able to show a real contribution to his work in socializing the Kalimasada program to the Genting Kalianak sub-district community to create an orderly population administration society.